DOES PRESENCE OF DOWN SYNDROME INCREASE RESPIRATORY SYNCYTIAL VIRUS (RSV) RELATED HOSPITALIZATION IN CHILDREN LESS THAN 2 YEARS OF AGE? A SYSTEMATIC REVIEW AND META-ANALYSIS. (18th May 2018) - Mitra, Souvik; McCord, Helen; El Azrak, Mohamed; Paes, Bosco
Abstract: BACKGROUND: Down syndrome (DS) is associated with a number of immunologic abnormalities and congenital heart disease (CHD) which increase susceptibility to respiratory syncytial virus (RSV). However current position statements from the American Academy of Pediatrics and the Canadian Paediatric Society do not recommend routine RSV prophylaxis with Palivizumab to all infants with DS, OBJECTIVES: To conduct a systematic reviewand meta-analysis of observational studies to compare RSV-related hospitalization (RSVH) rates, length of hospital stay(LOS), need for intensive care and assisted ventilation in DS children <2 years of age compared with children without DS. DESIGN/METHODS: Data Sources: The authors searched MEDLINE, Embase, CINAHL, reference lists of relevant articles, abstracts and conference proceedings, results of unpublished trials, and contacted the primary authors of relevant studies. Studies were included if data was provided on RSV-related hospitalization in children <2yr of age with and without DS. Data extraction & Synthesis: Two reviewers independently screened the search results, applied inclusion criteria and assessed methodological quality using the Newcastle-Ottawa Scale. Data was extracted and checked in duplicate. Main outcomes & measures: The primary outcome was RSV-related hospitalization. Secondary outcomes included length of hospital stay, need for intensive care and assisted ventilation. Sensitivity analysis was conducted for the primary outcome comparing DS infants without congenital heart disease (CHD) with non-DS infants. RESULTS: 19 cohort studies met the inclusion criteria. Ten studies involving 1, 390, 380 children were analyzed. DS-children had significantly higher RSVH compared to non-DS children (Relative Risk, 6.97; 95% CI, 6.01 to 8.08; I 2 =0%; Figure 1a). Among children hospitalized with RSV, need for assisted ventilation (RR, 5.82; 95% CI, 1.81 to 18.69; I 2 =84%; Figure 1b) and LOS (Mean difference, 2.28 days; 95% CI, 1.61 to 2.96 days; I 2 =0%; Figure 1c) were significantly higher in DS-children. The sensitivity analysis also confirmed that DS children without CHD had a significantly higher RSVH rate compared to non-DS children (RR, 6.31; 95% CI, 4.83 to 8.23;I 2 =0%; Figure 1d). CONCLUSION: Compared to children without DS, RSV-related hospitalization, need for assisted ventilation and length of RSV-related hospital stay is significantly higher in children with DS in the first 2 years of life. The results of this systematic review should prompt a favorable recommendation for routine RSV prophylaxis in both healthy and medically compromised DS children aged <2years.